Unbreakable [videorecording (DVD)] - Shyamalan, M. Night; Willis, Bruce, 1955-; Jackson, Samuel L.; Wright, Robin, 1966-; Clark, Spencer Treat, 1987- (Touchstone Home Entertainment, 2018)
After David Dunn emerges from a horrific train crash as the sole survivor, and without a single scratch on him, he meets a mysterious stranger. An unsettling stranger who believes comic book heroes walk the earth. A haunting stranger, whose obsession with David will change David's life forever.